1997
DOI: 10.1190/1.1444256
|View full text |Cite
|
Sign up to set email alerts
|

Imaging complex geologic structure with single‐arrival Kirchhoff prestack depth migration

Abstract: We compare various forms of single-arrival Kirchhoff prestack depth migration to a full-waveform, finitedifference migration image, using synthetic seismic data generated from the structurally complex 2-D Marmousi velocity model. First-arrival-traveltime Kirchhoff migration produces severe artifacts and image contamination in regions of the depth model where significant reflection energy propagates as late or multiple arrivals in the total reflection wavefield. Kirchhoff migrations using maximum-energy-arrival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…For example, prestack Kirchhoff migration with first arrivals does not always produce accurate (stacked) images in complex structure (Geoltrain and Brac, 1993;Gray and May, 1994). A number of authors have explored Kirchhoff migration with most energetic, as opposed to earliest, arrivals (Audebert et al, 1997). The examples presented by Operto et al (2000) suggest that even most energetic arrivals may not be sufficient to produce high quality images:…”
Section: Introductionmentioning
confidence: 99%
“…For example, prestack Kirchhoff migration with first arrivals does not always produce accurate (stacked) images in complex structure (Geoltrain and Brac, 1993;Gray and May, 1994). A number of authors have explored Kirchhoff migration with most energetic, as opposed to earliest, arrivals (Audebert et al, 1997). The examples presented by Operto et al (2000) suggest that even most energetic arrivals may not be sufficient to produce high quality images:…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the computation of the excitation-time table is performed before the monitoring stage. Loewenthal and Hu (1991) Audebert et al (1997) showed that Kirchhoff migration using maximum-energy travel time significantly improve the images quality especially in areas of complex structures compared to the first-arrival travel time.…”
Section: Imaging Steps In Electromagnetic Migrationmentioning
confidence: 98%
“…Its further approximation, choosing a single ray arrival of the complicated wavefield at each image location guarantees a noisy image in areas of many ray arrivals (Ettrich and Gajewski, 1996;Audebert et al, 1997;Thierry et al, 1999b;). Multiarrival Kirchhoff migration algorithms overcome this problem, but they tend to be complicated and relatively inefficient in three dimensions (Operto et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%